2000
DOI: 10.1021/tx990176i
|View full text |Cite
|
Sign up to set email alerts
|

Chemiluminescent Aldehyde and β-Diketone Reactions Promoted by Peroxynitrite

Abstract: Peroxynitrite is shown here to promote the aerobic oxidation of isobutanal (IBAL) and 3-methyl-2,4-pentanedione (MP) in a pH 7.2 phosphate buffer into acetone plus formate and biacetyl plus acetate, respectively. These products are expected from dioxetane intermediates, whose thermolysis is known to be chemiluminescent (CL). Accordingly, the extent of total oxygen uptake by IBAL at different concentrations parallels the corresponding CL maximum intensities. The pH profile based on oxygen uptake data for the MP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 44 publications
2
36
0
Order By: Relevance
“…This moiety undergoes thermolysis to two carbonyls, with one in an electronically excited triplet state having the high energy of a UV photon (> 3 eV, 70 kcal/mol, or 35,000 K) and capable of transferring its energy to DNA by a process that is independent of radiation (21). One of the few biologically-synthesized molecules that can initiate such “photochemistry in the dark” (22, 23) is peroxynitrite (ONOO – ) (24), which is generated by the reaction of O 2 •– with nitric oxide (NO • ). Peroxynitrite and NO • are stable enough to diffuse significant distances from the site of generation to the target molecule.…”
Section: Photochemical Pathwaymentioning
confidence: 99%
“…This moiety undergoes thermolysis to two carbonyls, with one in an electronically excited triplet state having the high energy of a UV photon (> 3 eV, 70 kcal/mol, or 35,000 K) and capable of transferring its energy to DNA by a process that is independent of radiation (21). One of the few biologically-synthesized molecules that can initiate such “photochemistry in the dark” (22, 23) is peroxynitrite (ONOO – ) (24), which is generated by the reaction of O 2 •– with nitric oxide (NO • ). Peroxynitrite and NO • are stable enough to diffuse significant distances from the site of generation to the target molecule.…”
Section: Photochemical Pathwaymentioning
confidence: 99%
“…However, a slightly different but significant profile was obtained by chemiluminescence, which reached a maximum around pH 7.2 and then declined with increasing pH. The roughly bell shaped pH curve obtained with EAA re- sembles the one reported for the acetoacetone/peroxynitrite system (29), suggesting dependence on H 2 PO 4 -(pK a ) 7.2) ion as an EAA enolization catalyst. Accordingly, as depicted in Figure 3, the light emission of the EAA/peroxynitrite system is also strongly dependent on the phosphate buffer concentration.…”
Section: Oxygen Consumption and Chemiluminescencementioning
confidence: 58%
“…While the observed light emission may also be explained by the Russell reaction of the alkylperoxyl intermediate shown in Scheme 2, this does not seem to be the case, because the extent of oxygen consumption by structurally similar carbonyl compounds should be almost the same. Little or no oxygen consumption was observed in the oxidation of acetaldehyde and isobutyraldehyde initiated by peroxynitrite (29), whereas EAA and MAA depleted the dissolved oxygen within seconds. It could also be argued that the disparate oxygen consumption by EAA is due to different nucleophilic addition efficiencies.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, it was also reported that the reaction of tryptophan with singlet oxygen also accompanied a chemiluminescence [35]. These chemiluminescence phenomena were considered as they originated from peroxidation and epoxidation of tryptophan by singlet oxygen and peroxynitrite [36,37]. Thus, The emitting species should be excited-state oxidation product resulted from decomposition of the formed dioxetane, epoxidized product of tryptophan by peroxynitrous acid [38,39], rather than the weak chemiluminescence of excited-state ONOOH * enhanced by tryptophan.…”
Section: Characteristics Of Chemiluminescencementioning
confidence: 99%